Hemospray for treatment of acute bleeding due to upper gastrointestinal tumours. Issue 5 (May 2017) - Arena, Monica; Masci, Enzo; Eusebi, Leonardo Henry; Iabichino, Giuseppe; Mangiavillano, Benedetto; Viaggi, Paolo; Morandi, Elisabetta; Fanti, Lorella; Granata, Antonino; Traina, Mario; Testoni, Pier Alberto; Opocher, Enrico; et al.
Abstract: Background: Hemospray is a new endoscopic haemostatic powder that can be used in the management of upper gastrointestinal bleedings. Aims: To assess the efficacy and safety of Hemospray as monotherapy for the treatment of acute upper gastrointestinal bleeding due to cancer. Methods: The endoscopy databases of 3 Italian Endoscopic Units were reviewed retrospectively and 15 patients (8 males; mean age 74 years) were included in this study. Results: Immediate haemostasis was achieved in 93% of cases. Among the successful cases, 3 re-bled, one case treated with Hemospray and injection had a good outcome, while 2 cases died both re-treated with Hemospray, injection and thermal therapy. No complications related to Hemospray occurred. Finally, 80% of patients had a good clinical outcome at 30 days and 50% at six months. Conclusion: Hemospray may be considered an effective and safe method for the endoscopic management of acute neoplastic upper gastrointestinal bleedings.